PENERAPAN MEDIA AUDIO VISUAL DALAM MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN FIQIH KELAS IX MATERI MAKANAN HALAL DAN HARAM DI MTS DDI ATTAQWA JAMPUE KABUPATEN PINRANG - Maryam; Saleh; Kahar; Ahdar; Marhani (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2025)
Effective learning is learning that is able to condition students to have motivation and enthusiasm for learning, one of the obligations of educators is to use the media in learning activities. Among the media in question is audio visual media. But in reality the learning system at MTs At-Taqwa DDI Jampue that teachers still have minimal use of audio visual media for Fiqh learning material. The formulation of the problem in this study were: 1) What is the implementation of learning by using Audio Visual Media on Jurisprudence in class IX in MTs At-Taqwa DDI Jampue? 2) How do you improve student learning outcomes in Jurisprudence in MTs At-Taqwa DDI Jampue after using audio visual media? This research was a classroom action research. Data was collected through observation and tests, the object of this research was students of class IXMTs At-Taqwa DDI Jampue, amounting to 15 students. This research was conducted in two stages, namely the first cycle and second cycle. At the first cycle stage the results of observations of student activities have a percentage of 65% and in the second cycle increased by 19% and have been very effective at 84%. While for student learning outcomes in the first cycle the average final test was 78.7 with a percentage of classical completeness of 70%. After a reflection of the implementation of the action, in the second cycle the average final test increased by 85.8 with the percentage of classical completeness of 93%. The results of research conducted by researchers prove that there is an increase in learning outcomes of students in participating in Fiqh learning through the use of audio-visual media.